PERISTILAHAN PERAWATAN TUBUH SECARA TRADISIONAL PADA MASYARAKAT MELAYU SAMBAS SEBAGAI MODEL PEMBELAJARAN BERBASIS TEKS - Uci Ulandari; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThis study was aimed to analyz the traditional terminology of body care in Sambas Malay society. Precisely in Tambatan Village, Sambas Regency. The problems discussed in this study were the form, lexical meaning, cultural meaning of traditional body care terminology in the Sambas Malay community, as well as the meaning and purpose of used the mantra in the activity. Then the implication is in language learning. The method in this study was a descriptive method. The approach isstructural, semantic, and ethnolinguistic. The source of the data was in the form of the informant's speech regarding the term of traditional body care. The data collection technique was skillful as the first technique, record, and record. Tool for collecting data from the researcher himself as a key instrument. The researcher managed to gather 140 terms and 7 traditional body care spells in the Sambas Malay community. The terminology consists of 33 terms in the form of monomorfemis, 74terms in the form of polymorphisms (30 terms in the form of endocentric phrases and 3 terms in the form of exocentric phrases), and 33 terms in the form. Then there are 140 terms that have lexical meanings and 63 terms have cultural meanings.Keywords: Sambas Malay Society , Traditional Body Care, Terminology